2021
DOI: 10.1177/10298649211055832
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of the classroom environment, student characteristics, and motivation for music lessons at secondary school

Abstract: The literature suggests that there is often no alignment between student preferences and what and how it is taught in the music classroom. A total of 749 Cypriot secondary school students, aged 12 to 14 years, responded to a survey addressing enjoyment of music, motivation for school music lessons, and perceptions of the music classroom environment. The survey included a questionnaire with six subscales: Involvement, Affiliation, Teacher Support, Task Orientation, Order and Organization, and Rule Clarity. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In fact, studies have focused on the association between autonomy support and enjoyment in music education. A study on music classroom education in secondary schools found a positive association between teachers' autonomy support and students' music enjoyment levels (Papageorgi and Economidou Stavrou, 2021). However, for music education, there is limited attention has been paid on the association between teachers' autonomy support and students' music enjoyment emotions in higher education and online education environment.…”
Section: Autonomy Support and Music Enjoymentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, studies have focused on the association between autonomy support and enjoyment in music education. A study on music classroom education in secondary schools found a positive association between teachers' autonomy support and students' music enjoyment levels (Papageorgi and Economidou Stavrou, 2021). However, for music education, there is limited attention has been paid on the association between teachers' autonomy support and students' music enjoyment emotions in higher education and online education environment.…”
Section: Autonomy Support and Music Enjoymentmentioning
confidence: 99%
“…Meanwhile, autonomy support has been recognized and used by music teachers for its potential to promote music learning (Evans, 2015). Although studies have demonstrated that teacher autonomy support in music education has a positive correlation with student enjoyment at the secondary level (Papageorgi and Economidou Stavrou, 2021), there is limited research on the association between teachers' autonomy support and students' music enjoyment in the form of online music education and also at the higher education level (Bonneville-Roussy et al, 2013). Therefore, this study will use the control-value theory of achievement emotions as a theoretical framework to validate the relationship between autonomy support and music enjoyment, and the mediating role of attribution and value, to understand the antecedents and consequences of music majors' enjoyment of music in online education and its mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have pointed out that participation in community music groups or musical activities such as music summer camps have an imperceptible and positive impact on career choices. 33 Second, in the classroom environment, students are able to experience higher levels of music enjoyment, participation and teacher support, which enhance motivation to learn 34 and could further predict aspirations of a music career. 1 Third, building off earlier studies, music broadcasting may possibly been seen as a type of music-rich resource in school context, which, similar to science-rich resources, 35 may link with students’ music feeling and encourage students to pursue a music-related occupation.…”
Section: Introductionmentioning
confidence: 99%
“… 39 As for the musical classroom which could improve students’ music skill by providing enough equipment, 40 their music motivation was increased by a musical classroom in which they could experience higher enjoyment of and engagement with music. 34 Furthermore, according to the social cognition theory which posits that environmental factors are the source of individual motivation and cognition, broadcasting in schools is an important offline platform for information dissemination 41 and to provide musical climate, playing an implicit role in students’ motivation to learn music. 42 Finally, music teachers could enhance students’ motivation and involvement in composition learning by helping students infuse their work with interests, experiences and so on.…”
Section: Introductionmentioning
confidence: 99%